Capital intelectual, capacidade absortiva individual e desempenho de inovação em uma instituição de ensino - Agostineto, Raquel Crestani (2019)
Institutions, whether public or private, are increasingly dependent on external knowledge to integrate their internal knowledge base. In view of that, the management of intellectual capital can collaborate with the dissemination of knowledge, as well as improve the performance of employees, through innovative tools, gradually required by public entities. Thus, the objective of this research was to analyze the existence of a relationship between intellectual capital, individual absorptive capacity and the innovation performance of technical-administrative staff of the Santa Catarina Federal Institute. To achieve the objective of this study, a self-administered questionnaire applied to the institution's technical-administrative staff was used as a data collection instrument, resulting in a sample of 314 respondents. Regarding data analysis, it was performed using descriptive analysis techniques - to verify the respondents' profile and calculate the individual absorptive capacity index - and structural equation modeling technique - to analyze the research hypotheses, which were supported, according to the path coefficients. The final quantitative analysis structure resulted in 28 variables, distributed among the constructs proposed by the research. The results showed that human capital, structural capital and relational capital influence individual absorptive capacity, from the perspective of the technical-administrative staff of the Santa Catarina Federal Institute, with the most relevant relationship being that of human capital. In addition, it was verified through the responses of the technical-administrative that the innovation performance - analyzed based on the creation of ideas and implementation of ideas - is influenced by the individual absorptive capacity. Therefore, through the results obtained, actions were proposed that may contribute to the influence between the constructs, and consequently, to individual and organizational performance.